2017
DOI: 10.1097/igc.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Diffusion-Weighted Magnetic Resonance Imaging and Diffusion Tensor Imaging Parameters Between Endometrioid Endometrial Adenocarcinoma and Uterine Serous Adenocarcinoma

Abstract: We suggest that both DWI and DTI could be used in distinguishing EEA from SA. Apparent diffusion coefficient and ADC possess potential diagnostic value with high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…[8][9][10][11][12][13][14] Therefore, our data support the observation that DTI is more accurate than conventional DWI for differentiating among histologic grades of carcinomas. Further, although a previous study has shown that DWI and DTI are useful for distinguishing between endometrioid endometrial adenocarcinoma and uterine serous adenocarcinoma, 30 it did not examine the usefulness of DTI maps for differentiating among histologic grades of EMACs; to the best of our knowledge, this is the first report to do so. We did not investigate the ability of DTI to distinguish the various subtypes of EMC because we did not have enough cases of nonendometrioid subtypes in our series.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14] Therefore, our data support the observation that DTI is more accurate than conventional DWI for differentiating among histologic grades of carcinomas. Further, although a previous study has shown that DWI and DTI are useful for distinguishing between endometrioid endometrial adenocarcinoma and uterine serous adenocarcinoma, 30 it did not examine the usefulness of DTI maps for differentiating among histologic grades of EMACs; to the best of our knowledge, this is the first report to do so. We did not investigate the ability of DTI to distinguish the various subtypes of EMC because we did not have enough cases of nonendometrioid subtypes in our series.…”
Section: Discussionmentioning
confidence: 83%
“…21,22 This may have affected calculations of eigenvalues and DTI parameters; nevertheless, the DTI parameters reported here are comparable with those reported in previous studies. 15,16,30 Our ultimate goal would be routine application of DTI in patients with EMC as a noninvasive method for obtaining vital tumor-related information to guide selection of optimal therapy within a clinically feasible duration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, magnetic resonance imaging (MRI) as a non-invasive preoperative risk assessment method that has been widely used in malignant tumors with functional and molecular imaging technology and reflects both the local and overall characteristics of lesions. The diffusion-weighted imaging (DWI) can identify the histological type of malignant tumor by diffusion of water molecules, which can be quantified by the apparent diffusion coefficient (ADC) value ( 10 , 11 ). Radiomics can extract features of medical images and transform them into quantitative data, reflecting the intensity, location, and spatial arrangement of voxels, which has been used to evaluate heterogeneity, aggressiveness, and prognosis of malignant tumors ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Zhao emphasized that DWI could be used for the differentiation of malignant epithelial and borderline ovarian tumors (24). In endometrial neoplasia, it has been reported that DWI can be used for the differentiation of malignant and benign endometrial tissues, as well as differentiation of endometrial serous and adenocancer (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%